USP42 protects ZNRF3/RNF43 from R-spondin-dependent clearance and inhibits Wnt signalling - Giebel, Nicole; Jaime-Soguero, Anchel de; García del Arco, Ana; Landry, Jonathan; Tietje, Marlene; Villacorta, Laura; Benes, Vladimir; Fernández-Sáiz, Vanesa; Acebron, Sergio P. (EMBO reports, 2021)
Abstract The tumour suppressors RNF43 and ZNRF3 play a central role in development and tissue homeostasis by promoting the turnover of the Wnt receptors LRP6 and Frizzled (FZD). The stem cell growth factor R-spondin induces auto-ubiquitination and membrane clearance of ZNRF3/RNF43 to promote Wnt signalling. However, the deubiquitinase stabilising ZNRF3/RNF43 at the plasma membrane remains unknown. Here, we show that the USP42 antagonises R-spondin by protecting ZNRF3/RNF43 from ubiquitin-dependent clearance. USP42 binds to the Dishevelled interacting region (DIR) of ZNRF3 and stalls the R-spondin-LGR4-ZNRF3 ternary complex by deubiquitinating ZNRF3. Accordingly, USP42 increases the turnover of LRP6 and Frizzled (FZD) receptors and inhibits Wnt signalling. Furthermore, we show that USP42 functions as a roadblock for paracrine Wnt signalling in colon cancer cells and mouse small intestinal organoids. We provide new mechanistic insights into the regulation R-spondin and conclude that USP42 is crucial for ZNRF3/RNF43 stabilisation at the cell surface.
Gesehen am 12.01.2022